2014
DOI: 10.1007/s10162-014-0445-0
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model Validates the Utility of Electrocochleography in Verifying Endolymphatic Hydrops

Abstract: Endolymphatic hydrops (ELH) is a disorder of the inner ear that causes tinnitus, vertigo, and hearing loss. An elevated ratio of the summating potential (SP) to the action potential (AP) measured by electrocochleography has long been considered to be the electrophysiological correlate of ELH-related clinical conditions, such as Meniere's disease, but in vivo confirmation and correlation between an elevated SP/AP ratio and ELH has not yet been possible. Confirming this relationship will be important to show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Multiple studies have characterized the postnatal development and disease manifestations in the Phex mouse [7,9,23,24,30,31]. At birth, the mice have normal inner ear histology including no ELH, spiral ganglion degeneration, or endolymphatic duct obstruction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have characterized the postnatal development and disease manifestations in the Phex mouse [7,9,23,24,30,31]. At birth, the mice have normal inner ear histology including no ELH, spiral ganglion degeneration, or endolymphatic duct obstruction.…”
Section: Methodsmentioning
confidence: 99%
“…Radiographic studies have also demonstrated dysmorphic temporal bones [21,22]. All of the otologic manifestations associated with XLH in humans have been replicated in the Phex mouse model, particularly the presence of diseased otic capsule bone and ELH [7,23]. …”
Section: Introductionmentioning
confidence: 99%
“…ELH has been associated with damage to the organ of Corti and spiral ganglion neurons (SGNs) and is the most well-studied mechanism of hearing loss in XLH [226, 236]. The severity of ELH has also correlated with the severity of hearing loss in Hyp-Duk mice [237].…”
Section: Background and Introductionmentioning
confidence: 99%
“…ABRs signals were acquired through intradermal needle electrodes (low impedance (< 5 kΩ), 25G needle diameter) directed to the ear canal of both ears. Ground electrodes were placed in the midline of the animal [ 25 ]. The brainstem signal in response to ipsilateral stimulation (right ear) was amplified 10,000–100,000 times and filtered between 0.3 and 3 kHz.…”
Section: Methodsmentioning
confidence: 99%